2018
DOI: 10.1111/jdv.14820
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exposome on acne

Abstract: Background Acne vulgaris is one of the main reasons for dermatological consultations. Severity and response to treatment may be impacted by various external factors or exposome.AimTo assess the impact of environmental factors on acne and to provide a comprehensive overview of the acne exposome.MethodsTwo consensus meetings of five European dermatologists and a comprehensive literature search on exposome factors triggering acne served as a basis for this review.ResultsAcne exposome was defined as the sum of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
110
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 124 publications
1
110
0
22
Order By: Relevance
“…While a familial predisposition has been linked to more frequent acne relapses, possibly related to a genetic component, 6 acne severity and response to treatment are impacted by numerous external factors. In a paper published in 2018, Dr eno et al 7 proposed the concept of acne exposome defining the sum of all environmental factors influencing acne occurrence, duration and severity. These exposome factors may be classified into six categories as follows: nutrition, medication, occupational factors, pollutants, climatic factors, and psychological and lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%
“…While a familial predisposition has been linked to more frequent acne relapses, possibly related to a genetic component, 6 acne severity and response to treatment are impacted by numerous external factors. In a paper published in 2018, Dr eno et al 7 proposed the concept of acne exposome defining the sum of all environmental factors influencing acne occurrence, duration and severity. These exposome factors may be classified into six categories as follows: nutrition, medication, occupational factors, pollutants, climatic factors, and psychological and lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The precise mechanism behind the onset of acne lesions is still not fully understood, and the role of Propionibacterium acnes is still largely discussed. [4,5] Although P acnes is observed in normal and acne skin, intense P acnes colonization of the sebaceous gland likely play a role in acne inflammation through bacterial antigens and creation of a biofilm. [4][5][6] The intense C acnes colonization causes inflammatory reactions and immune cell recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Although P acnes is observed in normal and acne skin, intense P acnes colonization of the sebaceous gland likely play a role in acne inflammation through bacterial antigens and creation of a biofilm. [4][5][6] The intense C acnes colonization causes inflammatory reactions and immune cell recruitment. [6] The bacteria's metabolism is also known to modify the skin's lipid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Addor et al, 2018 demonstrated significant changes in some of the mechanical properties of the stratum corneum by UV damage, reduce its cell cohesion and mechanical integrity; also affects the molecular structure of cell proteins and lipids [41]. This phenomenon is more marked in acne patients as the skin lipid film on the surface of the stratum corneum is altered through an increase in oxidized squalene and a decrease in linoleic acid [44]. Several experimental studies demonstrated the detoxifying activities of squalene against a wide range of chemicals such as arsenic and hexa-chloro-benzene [45].…”
Section: Introductionmentioning
confidence: 99%